FACILITATING A SHIFT TO COMPREHENSIVE CARER-LED ASSESSMENT IN PALLIATIVE HOME CARE: THE CSNAT APPROACH. Issue 1 (1st March 2014) - Austin, L; Ewing, G; Grande, G
Abstract : Introduction: The Carer Support Needs Assessment Tool (CSNAT) is an evidence based tool for comprehensive assessment of carers' needs. Use of the tool in practice requires a shift from informal practitioner-led methods of identifying carers' needs to a carer-led, practitioner-facilitated approach. Aim(s) and method(s): To identify training requirements to enable practitioners to move from practitioner-led to carer-led carer support needs assessment. The CSNAT was implemented in six palliative home care services as part of a stepped wedge cluster trial. Pre-implementation training was provided to practitioners at each site. Qualitative data were obtained on practitioners' experiences of implementing the CSNAT via focus groups, interviews and site visits/contacts (where field notes were made). Ongoing analysis identified challenges in adopting carer-led assessment and was used to revise training materials for subsequent training sessions. Results: The CSNAT was often perceived as a 'form' representing an 'add on' to usual practitioner-led practice. The training was therefore modified to promote the underlying principles of the 'CSNAT approach' (i.e. the process of carer-led assessment). The stages of the CSNAT approach comprise: Introducing the CSNAT, Carer's consideration of needs, The Assessment Conversation, Shared Action Plan and Shared Review. Each stage is facilitated by the practitioner, but led by the carer. Conclusion(s): Understanding of the CSNAT approach is fundamental to achieving carer- led assessment and support in palliative home care. The CSNAT approach resources are currently being tested as part of a CSNAT toolkit.